Phenomenological Study of Hemodialysis Therapy Compliance in Chronic Renal Failure Patients at El Syifa Hospital (Fresenius Kidney Care) Kuningan West Java - Ganjar Taufik; Ika Puspita Sari; Ika Yuni Astuti (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2021)
The problem of kidney failure patients in El Syifa Hospital (Fresenius Kidney Care) In Kuningan, West Java continues to increase year on year and in 2019 by 140. By 2020 it will increase to 155 sufferers. The data of patients undergoing hemodialysis therapy. The purpose of knowing the cause of the phenomenon of renal failure and along with factors that affect the non-compliance of kidney failure patients to perform hemodialysis therapy El Syifa Hospital (Fresenius Kidney Care) Kuningan West Java. The research design method used is descriptive with purpusive sampling. Research instruments in the form of interviews, data in Analysis by Colaizzi method, the results of the study data on the type of kemalin men 60% and women 40% Due to the habits of smoking, drinking fizzy drinks, and alcoholic beverages. The result data was obtained, irregular participants (70%), and the tertur (30%) irregularities include economic factors (44%), health (4%), support (10%), employment (4%). No symptoms (6%), personal agitation (2%), duration 5 hours, and with a duration of 2 x in 1 week.